The Influence of Promotional Strategies Through Social Media on Product Purchase Decisions Mediated by Word of Mouth Marketing - Singgih Nurgiyantoro (HM Publisher, 2021)
E-commerce is a sales system that developed after the invention of the internet. This kind of marketing or sales system can reach the whole world simultaneously without having to set up branch offices in all countries. In addition, it can also be done 24 hours without stopping. With only a computer unit connected to the internet, the company can market its products. Marketing with promotional strategies through the internet, especially with social media (social networks), can increase sales widely and does not require expensive marketing costs. Consumers will also find it easier to find information about the products they want to buy because they do not need to meet face to face directly. Word of mouth marketing often has a competitive advantage in conveying business information. This is because word-of-mouth marketing arises naturally from the opinion of the social environment, which is considered more honest, and there are no specific motives in conveying information to other consumers.